Comprehensive Analysis of Density of States (DOS), UV-Visible, NMR Spectroscopy, and Molecular Electrostatic Potential (MEP) of RU-486 and its Derivatives (Ph, KOH, NO?, OH) in Relation to Their Effects on Breast Cancer - Kebiroğlu, Mehmet Hanifi; Ak, Fermin (My University, 2025)
In this study, a comprehensive analysis was conducted on RU-486 (Mifepristone) and its derivatives (Ph, KOH, NO?, OH), focusing on their potential effectiveness against breast cancer. The analysis included Density of States (DOS) optimization, UV-Visible spectroscopy, Nuclear Magnetic Resonance (NMR) spectroscopy, and Molecular Electrostatic Potential (MEP) mapping. The electronic structures and stabilities of these molecules were examined through DOS, revealing how different functional groups influence their electronic properties. UV-Visible spectroscopy identified shifts in absorption maxima, which correspond to changes in electronic transitions due to functionalization. NMR spectroscopy provided insights into the chemical environments of specific nuclei, offering detailed information on molecular geometry and electronic distribution. MEP analysis mapped the electrostatic potential across the molecular surfaces, pinpointing regions of electrophilic and nucleophilic reactivity. Collectively, these analyses have enhanced the understanding of the electronic properties, reactivity, and potential pharmaceutical applications of RU-486 and its derivatives in breast cancer treatment.
Keywords: MEP; NMR; DOS; UV-Vis; Ru-486